Killi bir zeminin Tunçbilek uçucu külü kullanılarak stabilizasyonu - Aksoy, Hüseyin Suha; Yılmaz, Mehmet; Akarsu, Engür Esen (My University, 2008)
Bu çalışmada killi bir zemin, Tunçbilek uçucu külü ile stabilize edilmiştir. Killi zemine %0, %3, %5 ve % 10 oranlarında uçucu kül katılarak dört farklı numune elde edilmiştir. Optimum su muhtevasında hazırlanmış her bir numune üzerinde 1 günlük, 7 günlük ve 30 günlük serbest basınç deneyleri yapılmıştır. Uçucu kül ilavesi ile, zeminin plastisitesi pek değişmezken, optimum su muhtevası ve serbest basınç mukavemeti artan uçucu kül oranı ile artmıştır.

In this paper, the stabilization of a clayey soil with Tunçbilek fly ash was researched. Samples were prepared by using four different replacement amounts of 0%, 3%, 5% and 10% by weight of soil. All samples were prepared at optimum moisture content. All samples were sheared 1 day, 7 days and 30 days after preparation. Unconfined compression test were conducted on these samples. While plasticity of the soils not seriously affected by fly ash addition, optimum moisture content and strength of samples are increased.
Stabilization of a clayey soil with Tuncbilek fly ash
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Kil; Uçucu kül; Stabilizasyon; Mukavemet; Clay; Fly ash; Stabilization; Strength